Expression of the Drug-Dependent Antigen for Quinine-Dependent Antiplatelet Antibodies on GP III a but not that on GPI b, II b or IX on Human Endothelial Cells - Pfueller, Sharron L; Bilston, Robyn A; Jane, Stephen; Gibson, Jannine (Thrombosis and Haemostasis, 1990)
In quinine- and quinidine-induced thrombocytopenic purpura IgG antibodies are known to react in a drug-dependent manner with different combinations of surface glycoproteins (GP) Ib , IIb, IIIa and IX. Because endothelial cells share a number of properties of platelets, including the presence of GP Ilia and GPIb-like proteins, we have compared these two cell types for their quinine-dependent IgG binding abilities. By immunoblotting of endothelial cells, quinine-dependent IgG binding from four patient sera was observed only to a 93 kDa component corresponding to GP Ilia. Strong IgG binding independent of the drug was found at 170–180 kDa. Thus endothelial cells express the GP Ilia quinine-dependent epitope on platelet GP IIIa , but not those on other platelet glycoproteins.